2019
DOI: 10.1002/ps.5701
|View full text |Cite
|
Sign up to set email alerts
|

Silencing arginine kinase/integrin β1subunit by transgenic plant expressing dsRNA inhibits the development and survival of Plutella xylostella

Abstract: Background Plutella xylostella is a devastating agricultural insect pest of cruciferous plants, including crops. Plant‐mediated RNA interference (RNAi) is currently being developed for plant protection. In this study, we investigated the response of P. xylostella exposed to transgenic Arabidopsis thaliana plants that expressed double‐stranded RNA (dsRNA) targeting P. xylostella genes of arginine kinase (PxAK) and integrin β1 subunit (Pxβ). RESULTS Transgenic plants producing dsRNAs of the 384‐bp fragment of Px… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…To further understand the function of Px⊍E8 in multi-resistance, expression of Px⊍E8 was knocked down in GD-2019 by RNAi and its resistance to the five insecticides was tested. Posttranscriptional gene silencing by RNAi is an effective tool to investigate the functions of individual genes, 41,42 and has been widely used to study the roles of detoxifying enzyme genes in insecticide resistance. [43][44][45][46] Repression of Px⊍E8 by RNAi reduced CarE activity and resistance to beta-cypermethrin and phoxim, which gave further proof that overexpression of Px⊍E8 was involved in phoxim and beta-cypermethrin resistance in P. xylostella.…”
Section: Discussionmentioning
confidence: 99%
“…To further understand the function of Px⊍E8 in multi-resistance, expression of Px⊍E8 was knocked down in GD-2019 by RNAi and its resistance to the five insecticides was tested. Posttranscriptional gene silencing by RNAi is an effective tool to investigate the functions of individual genes, 41,42 and has been widely used to study the roles of detoxifying enzyme genes in insecticide resistance. [43][44][45][46] Repression of Px⊍E8 by RNAi reduced CarE activity and resistance to beta-cypermethrin and phoxim, which gave further proof that overexpression of Px⊍E8 was involved in phoxim and beta-cypermethrin resistance in P. xylostella.…”
Section: Discussionmentioning
confidence: 99%
“…We observed that the thorax and abdominal regions of P. xylostella larvae appeared to exhibit typical shrinkage, some larvae failed to exuviate and some pupae could not break out after 8010AKi or BMB171AKi treatment, which was probably caused by the disorder of energy metabolism for muscle development after Px AK was inhibited. Similarly, ingestion of transgenic plants expressing dsRNA of AK significantly retards the larval growth and development and even causes the death in Helicoverpa armigera Hübner (Lepidoptera: Noctuidae) [ 8 ] and P. xylostella [ 9 ]. Generally, insect pests die with a brown or black body after Bt infection [ 29 ], which was also observed in dead P. xylostella larvae after 8010AKi treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The same phenomena are reported in dsRNA-expressed transgenic plants, such as Solanum tuberosum Linnaeus [ 5 ], Nicotiana tobacum Linnaeus and Gossypium hirsutum Linnaeus cv. Xu-142 [ 7 ], and Arabidopsis thaliana (Linnaeus) Heynhold [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decades, RNAi techniques have emerged as an eco-friendly, efficient, and reliable platform for the development of GM insecticidal plants (Mao et al 2007 ; Bachman et al 2013 ; Ni et al 2017 ; Poreddy et al 2017 ; Fu et al 2019 ; Darsan Singh et al 2019 ). These plants harbor double-stranded RNAs (dsRNAs) that can target and suppress mRNA levels through the RNAi pathway and lead to insect morbidity or mortality (Zhang et al 2017 ).…”
Section: Discussionmentioning
confidence: 99%